Porous Cu/YSZ anodes processed by aqueous tape casting for IT-SOFC. Issue 16 (December 2017) - Amaya, Diana M.; Estrada, Daniel; Hotza, Dachamir; Rodrigues Neto, João B.; Escobar, Jairo A.
Abstract: Porous copper/yttria-stabilized zirconia (Cu/YSZ) thin tapes were produced to be used as anodes in intermediate temperature solid oxide fuel cells (IT-SOFC). The use of copper in these cermets promises a better chemical resistance and a lower operating temperature for SOFC. Graphite and cassava starch were used as pore forming agents, which led to porosity values between 30 and 40%. Tapes were obtained by aqueous tape casting with controlled thickness (300–2000 μm). Before casting, CuO/YSZ aqueous suspensions were formulated based on rheological characterization. Sintering was carried out at 1150 °C during 1 h. Cu/YSZ tapes were obtained after redox reaction, performed at 400, 600 and 800 °C.